Researching the capabilities of people with disabilities: would a critical realist methodology help?. Issue 2 (15th March 2021) - Ton, Khanh That; Gaillard, J. C.; Adamson, Carole; Akgungor, Caglar
ABSTRACT: Amartya Sen's capability approach is often used in disability research as a normative framework for describing and evaluating the well-being of people with disabilities. Nevertheless, recently, the possibility of going beyond description to the use of the capability approach as an explanatory tool has been raised. However, to allow the use of the capability approach in this way requires grounding it in an appropriate research paradigm. In this paper, critical realism is adopted for this purpose. It is argued that critical realism can provide the ontology needed to justify finding explanations for the way that people with disabilities achieve their valued capabilities. The assumption here is that there are real, emergent structures and mechanisms that underlie empirical capabilities; and that these structures and mechanisms are related to people's agency, as described by critical realism's conception of the relationship between structure and agency.